Forgotten families ending the growing crisis confronting children and working parents in the global economy - Heymann, Jody, 1959- (Oxford : Oxford University Press, 2006)
Based on extensive survey data, this book offers a global account of how the changing conditons of work threaten children women & men, & the infirm, addressing problems facing both industrialized & developing countries alike.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Work and family; Dual-career families; Children of working parents; Globalization -- Social aspects